African film : new forms of aesthetics and politics - Diawara, Manthia (Prestel, 2010)
Contemporary African filmmaking is the subject of this insightful and exciting look at every aspect of the art form on the African continent. Focusing on new trends in African cinema from the 1990s to today, this book explores new cinematic languages and modes of production, films departure from nationalism and social realism, and the Nollywood film industry, among other topics. In this book Manthia Diawara, a renowned scholar on Black cinema, literature, and art brings readers up to date on the exciting changes taking place behind and in front of African cameras. Contributions by filmmakers, scholars, and producers as well as profiles of thirty important African directors and their films, provide valuable insight into recent developments. The volume comes with a DVD containing several interviews with filmmakers conducted by the author. Scholars, students, and anyone interested in cinematic and African cultural studies will find much to discover and celebrate in this authoritative, fascinating look at new trends in African filmmaking.